Oral birch pollen immunotherapy with apples: Results of a phase II clinical pilot study. Issue 2 (23rd February 2021) - Nothegger, Bettina; Reider, Norbert; Covaciu, Claudia E.; Cova, Valentina; Ahammer, Linda; Eidelpes, Reiner; Unterhauser, Jana; Platzgummer, Stefan; Raffeiner, Elisabeth; Tollinger, Martin; Letschka, Thomas; Eisendle, Klaus
Abstract: Background: Seventy percent of patients suffering from birch pollen allergy (BPA) develop a pollen‐related food allergy (prFA), especially to apples, due to a clinically relevant cross‐reactivity between the major allergen in birch Bet v 1 and Mal d 1 in apples. Therefore allergen‐specific immunotherapy with fresh apples (AITA) could be a promising natural treatment of both BPA and prFA. Objective: To assess the clinical efficacy of immunotherapy by daily apple consumption for patients with BPA and prFA. Methods: A daily defined increasing amount of selected cultivars (Red Moon®, Pink Lady®, Topaz, Golden Delicious) was continuously consumed by 16 patients (12 female; median age; 50; range, 23–68 years), leading to increased intake of allergen over a period of at least 8 months. Specific IgE and IgG4 to Bet v 1 and Mal d 1, conjunctival and oral provocation tests, skin reactivity, and the average daily rhinoconjunctivitis combined symptom and medication score (CSMS) were measured during the peak birch pollen season. Results: After 8 months of therapy, patients showed increased tolerance to apples ( p < .001) and a decreased skin reactivity to apples. Oral allergy syndrome to other birch prFA than apple also decreased ( p < .05). Moreover, daily rhinoconjunctivitis CSMS declined by 34% ( p < .001), as did conjunctival reactivity to birch pollen extract by 27% ( p < .01), while specific IgG4 to Mal d 1 and Bet v 1 increased ( p < .01). Abstract : A 70% of patients suffering from birch pollen allergy (BPA) develop a pollen‐related food allergy (prFA), especially to apples. This is due to a strong clinically relevant homology between the major allergen in birch Bet v 1 and Mal d 1 in apples. Therefore a pilot trial using fresh apples for allergen‐specific immunotherapy to birch pollen was performed. After 8 months of therapy, patients showed increased tolerance to apples and other birch pollen‐related food allergens. Moreover, daily rhinoconjunctivitis combined symptom and medication score (CSMS) declined by 34% ( p < .001), as did conjunctival reactivity to birch pollen extract by 27% ( p < .01), while specific IgG4 to Mal d 1 and Bet v 1 increased ( p < .01). In this small pilot trial daily apple consumption improved both birch pollen and related food allergies. If confirmed by a larger controlled trial apples could provide a natural, healthy and cost‐saving causal treatment for BPA.